Formula Optimization and Activity Test In Vitro Lotion O/W Ethanolic Extract of Mangga Temperature (Curcuma Mangga Val. and Van Zijp) as Solar Tables - Mercy Arizona; A. Karim Zulkarnain (Majalah Farmaseutik, 2018)
Intersection mango extract (Curcuma mango Val.) Has activity as a sunscreen by spectrophotometry. This study aims to determine the optimum formula lotion o/w, properties and physical stability of the optimum formula lotion o/w, and the activities of the optimum formula sunscreen lotion o/w Intersection mango extract (Curcuma mango Val.) by spectrophotometry. The optimum formula was obtained by the method Simplex Lattice Design (SLD). Responses are used to determine the optimum formula is the bonding strength and viscosity. Physical stability lotion o/w at room temperature include tests dispersive power, adhesion, and viscosity, as well as freeze thaw cycling test. Activities sunscreen lotion o/w determined by spectrophotometry to determine the Sun Protecting Factor (SPF),% transmission erythema, and% transmission pigmentation. Data were analyzed by One Way ANOVA and t test. The results showed that the optimum formula lotion o/w on a combination of 5% triethanolamine (TEA) -stearat and 5% cetyl alcohol. Lotion o/w intersection mango extracts have had the scatter 63.21 ± 2.69 cm2, the stickiness of 2.32 ± 0.15 seconds, and the viscosity of 133.5±8.05 dPas. Results of statistical analysis showed that the lotion o/w has good stability. Lotion o/w has activity as a sunscreen lotion at concentrations o/w 12.5% are indicated with an SPF value of 12.82 ± 0.16 and ineffective in the protection against erythema and pigmentation.